AB0584 JOINT PROFILE OF BEHÇET'S DISEASE. (June 2019) - Farhat, Amel; Baccouche, Khadija; Achek, Mohamed Amine EL; Amri, Nejla El; Zeglaoui, Hela; Bouajina, Elyes
Abstract : Background: Joint manifestations during Behçet's disease (BD) are frequent and polymorphic. Objectives: To analyze these manifestations through 41 cases. Methods: A retrospective study of 41 patients, collected at the rheumatology department of Farhat Hached University Hospital over a period of 19 years, meeting the criteria of the international study group on BD. Results: 41 patients with a mean age of 40.21 years [16-66] were collected. The sex ratio=2.41. The articular and mucocutaneous involvement were constant. Also were found ocular manifestations (5cas), neurological (1cas), cardiac (1cas), gastro-intestinal (1cas), venous thrombosis (5 cases), arterial thrombosis (1 case) and an aneurysm (2 cases). Joint involvement was revealing in 21 cases (51.2%) occurring during evolution in 20 cases with an average delay of 102 months [6-360]. The most frequent manifestations were arthralgia in 24 cases (58.5%) and arthritis in 17 cases. It was predominantly asymmetric (21 cases), mono articular (13 cases), oligoarticular (16 cases) and polyarticular (12 cases). The knees and ankles were the most affected joints in 32 cases and 25 cases respectively, followed by wrist involvement (12 cases), MCP (5 cases) and elbows and shoulders in 4 cases each. A knee flessum was found in 2 cases. X-rays were mostly normal (35 cases). They showed erosive involvement (1case), joint narrowing (1case), osteonecrosis (2cases) and sacroiliitis (2cases). The presence of a popliteal cyst was noted in 2 cases. Conclusion: Joint manifestations during the BD can be inaugural and take on several clinical aspects. They usually heal without sequelae and do not engage functional prognosis with the exception of rare cases of destructive arthritis. Disclosure of Interests: None declared